2014
DOI: 10.1007/s11999-013-3377-9
|View full text |Cite
|
Sign up to set email alerts
|

What is the Prognosis of Revision Total Hip Arthroplasty in Patients 55 Years and Younger?

Abstract: Background Revision THAs are expected to increase; however, few studies have characterized the prognosis of revision THAs in younger patients. Questions/purposes We performed a case-control study to evaluate intermediate-term survivorship, complications, and hip and activity scores after revision THAs in patients 55 years and younger, compared these outcomes with the results of primary THAs in a matched patient population, and evaluated risk factors for failed revisions.Methods Ninety-three patients (103 hips)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…But these events are also very costly to society with increased medical costs, sick leave, etc. It has also been reported that results following revision surgery are less likely to be as good as the first operation [7].…”
Section: Introductionmentioning
confidence: 99%
“…But these events are also very costly to society with increased medical costs, sick leave, etc. It has also been reported that results following revision surgery are less likely to be as good as the first operation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Each author certifies that his or her institution approved or waived approval for the reporting of this case and that all investigations were conducted in conformity with ethical principles of research. 20 years [1,26,40]. Despite the clinical success of the arthroplasties, aseptic loosening is one of the major causes of failure [29,45].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study that describes satisfying results of revision THA performed in patients aged < 55 years. This study fills a gap in the revision THA literature, because the reported results in younger patients have been disappointing until now [ 1 , 16 , 22 ]. The 10-year survivorship was 97% for rerevision for aseptic loosening and 87% for rerevision for any reason.…”
Section: Discussionmentioning
confidence: 97%
“…This comparable to the improvement in clinical scores reported by other revision series performed in younger patients. Adelani et al [ 1 ] reported a mean improvement in HHS of 19.2 points and Lee et al [ 22 ] reported an improvement of 36 points in the modified HHS (no physical examination is necessary for this modified scoring system).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation